Pendampingan Hukum Oleh Paralegal Sebagai Upaya Peningkatan Akses Keadilan - Nugraha, Naufal Satria; Firmansyah, Amelinda Safira; Wijayanti, Zulfa Rena; Wildan, Muhammad; Ramadan, Daud Renata Candra (Media Hukum Indonesia (MHI), 2025)
This study examines the strategic role of paralegals and legal teams in providing legal assistance to the poor as a manifestation of the principles of the rule of law and social justice. Through a consultative, educational, and mediative approach, paralegals seek to bridge the gap between marginalized communities and the formal legal system. Despite their significant contribution, the legal position of paralegals still faces challenges, especially after the Supreme Court Decision Number 22P/HUM/2018 which limits their authority to non-litigation legal assistance. This limitation creates legal uncertainty and hinders the effectiveness of the assistance provided. This study emphasizes the need for more comprehensive regulations to clarify and strengthen the position of paralegals, including legal protection in carrying out their duties. In addition, increasing capacity through ongoing training and collaboration between the government, legal aid organizations, and legal education institutions is crucial to realizing equal access to justice for all levels of society. Thus, paralegals can carry out their roles effectively and professionally in the Indonesian legal system.